1982
DOI: 10.1016/0014-5793(82)80176-2
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐affinity labelling of the thyrotropin receptor

Abstract: Thyrotropin-thyrotropin receptor complexes Disulphide-linked subunit (SDS-polyacrylamide gel electrophoresis)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 7 publications
3
33
0
Order By: Relevance
“…These bands had M, values of 70500 and 85500 in the case of guinea pig fat and 74000 and 88000 in the case of guinea pig thyroid soluble receptors (table 1). A& values of 59000 and 74000 for porcine thyroid preparations have been reported in [7]. The higher M, bands were not observed when an excess of unlabelled TSH was added to the incubation mixture prior to [ fig.2).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…These bands had M, values of 70500 and 85500 in the case of guinea pig fat and 74000 and 88000 in the case of guinea pig thyroid soluble receptors (table 1). A& values of 59000 and 74000 for porcine thyroid preparations have been reported in [7]. The higher M, bands were not observed when an excess of unlabelled TSH was added to the incubation mixture prior to [ fig.2).…”
Section: Resultsmentioning
confidence: 81%
“…Previous studies [7] have indicated that the two bands differing in M, by 14000 which comprise the components of the TSH-TSH receptor complexes observed on SDS-PAGE under reducing conditions represent a single subunit of the TSH receptor (designated the A subunit) cross-linked to (i) one subunit of TSH (lower A4, band) or to (ii) two subunits of TSH (higher M, band) where the TSH subunits are themselves cross-linked so dissociation cannot occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-linking analysis of the CGRP-receptor complex in intact placental membrane preparations or soluble receptor preparations was performed using ' 251-a-CGRP and the homolifunctional cross-linking disuccinimidyl suberate (DSS) essentially as described by Buckland et al [34]. Reaction conditions were as described for receptor binding, except that 50 mM Hepes pH 7.6 was substituted for Tris in buffer A.…”
Section: Cross-linking Analysesmentioning
confidence: 99%